2016
DOI: 10.1111/gcbb.12404
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Miscanthus sinensis in US naturalized populations

Abstract: Miscanthus is increasingly gaining popularity as a bioenergy grass because of its extremely high biomass productivity. Many clones of this grass were introduced into United States over the past century from East Asia where it originated, and planted for ornamental and landscaping purposes. An understanding of the genetic diversity among these naturalized populations may help in the efficient selection of potential parents in the Miscanthus breeding program. Here, we report our study analyzing the genetic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
(58 reference statements)
1
13
1
Order By: Relevance
“…In this study, the mean of genetic diversity within each population was 0.32, which was similar to Chinese and U.S. M . sinensis although different markers were used in these study [23, 24, 64], and higher than previous measurements from cross-pollinated plants ( He = 0.162) and monocotyledons ( He = 0.181) [59, 65]. At the species level, the genetic diversity of M .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, the mean of genetic diversity within each population was 0.32, which was similar to Chinese and U.S. M . sinensis although different markers were used in these study [23, 24, 64], and higher than previous measurements from cross-pollinated plants ( He = 0.162) and monocotyledons ( He = 0.181) [59, 65]. At the species level, the genetic diversity of M .…”
Section: Discussionmentioning
confidence: 93%
“…The greater similarity of populations among rather than within individuals indicated that these populations were probably founded by many individuals and that there were high levels of gene flow among populations. Cross-pollinated plants often show huge variation within populations and a lower level of variation between populations [24, 25, 63]. Genetic variation of US naturalized populations of M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural composition was gathered from previous studies; and their conversion rates were obtained from NREL recent study …”
Section: Methodsmentioning
confidence: 99%
“…Miscanthus sinensis Andersson (Chinese silvergrass) is an herbaceous perennial grass native to Eastern Asia. It is naturalized in parts of the United States [ 1 ] and is currently being investigated for bioenergy [ 2 ] and sugarcane breeding purposes [ 3 ]. Miscanthus sinensis is susceptible to several diseases caused by viruses, including: sorghum mosaic virus [ 4 ], switchgrass mosaic virus [ 5 ], and barley yellow dwarf virus [ 6 , 7 ] and can also serve as a host to the aphid species Rhopalosiphum maidis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%